Cross-cultural adaptation and validation of the PedsQL™ stem cell transplant module in China: A methodological and cross-sectional study - Wei, Yuting; Zhang, Heng; Qian, Xiaowen; Xue, Yao; Rong, Liucheng; Wang, Yaping; Jiang, Wenjin; Lin, Rufeng; Lu, Shifeng; Zhai, Xiaowen; Fang, Yongjun (Frontiers in Pediatrics, 2023)
Background: Hematopoietic stem cell transplantation (HSCT), as a mature technology, has significantly improved the survival rate of children. However, there lack efficient scales to assess the quality of life (QoL) of children with HSCT in China, which has important implications in the care of this population. This study aimed to translate the original English Pediatric Quality of Life InventoryTM (PedsQL™) Stem Cell Transplant Module into a Chinese mandarin version, and evaluate its reliability. Methods: Children of ages 2 to 18 years who had received HSCT at Children’s Hospital of Nanjing Medical University and Children’s Hospital of Fudan University were recruited. Children or their parents were asked to fill the PedsQL™ 4.0 Generic Core Scales, PedsQLTM Stem Cell Transplant Module, and PedsQL™ Family Information Form. Feasibility was evaluated by completion rate and the percentage of missing items, reliability by the internal consistency and test-retest reliability, and validity by factor analysis and correlation analysis between the scores of total scale and each dimension. Results: A total of 120 children (mean age 6.37, SD = 3.674) and some parents were included. A low percentage of items were missed in returned reports. Cronbach’s alpha coefficient reached 0.70 in the majority of dimensions of both child self-report and parent proxy-report. Test-retest reliability was 0.685 in parents’ forms and 0.765 in child’s forms. Eight factors were extracted, with a cumulative contribution rate of 74.54%. The correlation between PedsQL™ 4.0 and Transplant Module was 0.748 for children self-report and 0.808 for parent proxy-report. Conclusions: This study provides evidence that the Chinese mandarin version of the PedsQLTM Stem Cell Transplant is feasible, reliable and valid in evaluating the QoL of Chinese children after HSCT.